ANALYSIS OF ENVIRONMENTAL CONCERN ATTITUDE AND ENVIRONMENTAL AWARENESS OF GRADE IV STUDENTS OF STATE ELEMENTARY SCHOOL 233 PALEMBANG - Lusita, Henora; Sukardi, Sukardi; Kusuma Putri, Mega (Cerdas Proklamator, 2025)
This study aims to determine the Analysis of Environmental Awareness and Environmental Awareness of Grade IV students of State Elementary School 233 Palembang. This study uses a qualitative descriptive research method. Data collection techniques used are teacher interviews, student questionnaires, and documentation. Data analysis techniques used are data reduction, data presentation, and conclusion drawing. The results of the study show that the Analysis of Environmental Awareness and Environmental Awareness of Grade IV Students of State Elementary School 233 Palembang is very good and quite concerned about the environment in the school. This caring attitude and environmental awareness are the keys to creating a clean and healthy environment, although there has been progress in students' concern for the environment, collaborative efforts are still needed from individuals, families, schools and the government by providing trash bins in every place that has been provided by the school. Keywords: Environmental Awareness and Environmental Care